Caracterización de sistemas de producción bovina en el distrito de Barranquita - San Martín 2018 - Roque Valderrama, Rosmery (2019)
The objective of the professional sufficiency work was to evaluate the characterization of bovine production systems in the district of Barranquita-San Martin 2018. The results indicated an average livestock experience of 37 years and the farms have between 67-120 has with cut grass (Pennisetum purpureum Schumach) 20 has and 42-92.25 has/fundo of natural pastures such as torourco (Axonopus compresus, Paspalum conjugatum and Axonopus guianensis). The construction of stables varies between 0.25-0.75 ha/farm and warehouses and silos between 0.25-0.50 ha/farm. The cultivated or monoculture areas are 8-30 ha/farm and the forests are 10-30 ha/farm. The improved pasture is Brachiaria brizhanta, with 3-6/pastures/fundo. They use electric fencing and barbed wire for animal control. Meat and milk are produced; the average age at first service is from one year and eight months to two and a half years; the average age for the first childbirth of 2.5-3 years; they come into heat after giving birth at three months; the breeding male is replaced every three years; they use manual milking once a day, 2.1 to 3.8 liters/milk/cow; cows in production from 12-40. Milk is sold to the public both fresh and processed (cheese). The extensive and semi-stalled exploitation systems, some provide supplementation of one kilogram of concentrate/cow with common and mineral salt, based on rice powder, soybean cake, corn, calcium carbonate and monocalcium phosphate. They are vaccinated against symptomatic anthrax and dewormed against endo and ectoparasites and multivitamins are applied; They use the Parasitological Diagnosis Plan. The frequent diseases are: mastitis, metritis, intestinal parasitism and ectoparasites (myiasis, ticks, etc.). The farm's income comes from agriculture, pig raising, trade and education. Technical assistance is limited, and they are associated, requiring productive projects, training courses and professional advice.